(NiZ ISTORII SKRIPI^NOJ PEDAGOGIKI(B.s (NU^EBNOE POSOBIE(B.s - (Ni(B.(Np(B.(NbLAGOWE]ENSKIJs ((NmINSK(B.s (NwY[EJ[AQ [KOLA(B.s, 1980)
(NkNIGE PREDNAZNA^ENP DLQ STUDENTOW KONSERWATORJ I U^A]IHSQ MUZYKALXNYH U^ILI] W KA^ESTWA U^EBNOE POSOBIE(B.s
Keywords: (NmETODIKAs